Governance, Trust and Elites in Sub-Saharan Africa : Madagascar in a Comparative Perspective - (:unkn) unknown (My University, 2024)
This thesis studies governance through three approaches: its measurement, the relationship between its components, and its actors. It focuses on Sub-Saharan Africa, with particular attention to Madagascar, whose puzzling economic path has been mainly shapedby its governance dynamics and the behaviors and strategies of its elites. The chapters primarily rely on unique and firsth and household surveys reporting individual perceptions and experiences of governance, peace, and security (GPS-SHaSA; “Pouvoiret Citoyens”). Additional key community and household living condition surveys have also been mobilized. Chapter 1 investigates the correlations between perception and experience indicators across three governance dimensions: corruption, crime, and discrimination, focusing primarily on Madagascar compared to eight other Sub-Saharan countries. Chapter 2 analyzes the impact of the State presence through public services on institutional trust in Madagascar. Chapter 3 examines the profiles and potential returns of elite networks held by citizens in Madagascar.
Keywords: African Research